Analisis Survival Model Regresi Cox Pada Lama Waktu Sembuh Pasien Gejala Sedang Covid-19 - Sulantari Sulantari; Wigid Hariadi (Mathematics Department, Faculty of Mathematics and Sciences Unisda Lamongan, 2022)
Survival analysis Model is one of the statistical analysis that can be used to test the survival function of an event. Survival analysis can be applied to health cases. The Kaplan-Meier test and cox proportional hazard regression analysis are part of the survival analysis. One of the health problems that Indonesia and the world are facing today is the virus covid-19 case. The country of Indonesia is one of the countries that experienced the impact of the virus covid-19. In Jember Regency, as of October 23, 2020, the number of patients who were confirmed positive was 1,098 patients with 85.52% having recovered, and 5.01% having died. Seeing the high number of positive cases of Covid-19 in Jember Regency, the authors want to conduct a study on the survival analysis of cox regression model on the long time of recovery of patients with moderate symptoms of covid-19 in the Jember region, especially in RSD Dr. Soebandi Jember. The results of this analysis are: (1) survival function of patients with moderate symptoms of Covid-19 at RSD dr Soebandi Jember, for female patients, it has a faster recovery time than patients with male sex. (2) survival function of patients with moderate symptoms of Covid-19 at RSD dr Soebandi Jember, for patients who do not have comorbid have a longer recovery time faster than patients who have comorbid. And (3) the variables of sex and comorbid status affect the length of time to recover patients with moderate symptoms of covid-19 at RSD Dr. Soebandi Jember. With the likelihood ratio (LRT) is 3.5255 for gender variables, and 16.5221 for comorbid status variables Abstrak Model analisis survival adalah salah satu analisis statistik yang dapat digunakan untuk menguji fungsi survival suatu kejadian. Analisis survival dapat dapat diterapkan pada kasus kesehatan. Uji Kaplan-Meier dan analisis regresi cox proporsional hazard merupakan bagian dari analisis survival. Salah satu permasalahan kesehatan yang sedang dihadapi Indonesia dan Dunia saat ini adalah kasus virus covid-19. Negara Indonesia merupakan salah satu Negara yang mengalami dampak virus covid-19. Di Kabupaten Jember, per-tanggal 23 Oktober 2020, jumlah pasien yang terkonfirmasi positif sebanyak 1.098 pasien dengan 85,52% telah sembuh, dan 5,01% meninggal dunia. Melihat tingginya kasus positif Covid-19 di Kabupaten Jember, maka penulis ingin melakukan penelitian tentang analisis survival model regresi cox pada lama waktu sembuh pasien gejala sedang covid-19 di Wilayah Jember, khususnya di RSD dr Soebandi Jember. Hasil dari analisis ini yakni: (1) fungsi survival pasien gejala sedang Covid-19 di RSD dr Soebandi Jember, untuk pasien jenis kelamin perempuan memiliki lama waktu sembuh yang lebih cepat dibandingkan pasien dengan jenis kelamin laki-laki. (2) fungsi survival pasien gejala sedang Covid-19 di RSD dr Soebandi Jember, untuk pasien yang tidak memiliki comorbid mempunyai lama waktu sembuh yang lebih cepat dibandingkan pasien yang memiliki comorbid. Dan (3) variabel jenis kelamin dan status comorbid berpengaruh terhadap lama waktu sembuh pasien gejala sedang covid-19 di RSD dr Soebandi Jember. Dengan nilai likelihood rationya (LRT) adalah sebesar 3.5255 untuk variabel jenis kelamin, dan 16.5221 untuk variabel status comorbid.